Penerapan Metode Word Square dalam Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan Tentang Keutuhan Negara Kesatuan Republik Indonesia (NKRI) pada Peserta Didik Kelas V SDN Pacar - E Puji Lestari (Jurnal Pendidikan Dasar, 2019)
Abstract. The purposes of this research are to describe the application of Word Square Method in Civil Education learning about the Integrity of the Unity Republic of Indonesia on the Fifth Class students of Pacar Elementary School on the First Semester of the 2017/2018 Year Academic and to analyze the increasing of the learning result in Civil Education learning about the Integrity of the Unity Republic of Indonesia on the Fifth Class students of Pacar Elementary School on the First Semester of the 2017/2018 Year Academic with Word Square Method. The type of this research is a Classroom Action Research (CAR). The subjects are 25 students. The conclusions of this research are 1) the application of Word Square Method inCivil Education learning about the Integrity of the Unity Republic of Indonesia on the Fifth Class students of Pacar Elementary School is using a group study approach in a small group and working the group task of Word Square and 2) the application of Word Square Method is increasing the learning result in Civil Education learning about the Integrity of the Unity Republic of Indonesia on the Fifth Class students of Pacar Elementary School.